Computational studies of DNA sequencing with solid-state nanopores: key issues and future prospects - Tu, Yaoquan (Frontiers in Chemistry, 2014)
Owing to the potential use for real personalized genome sequencing, DNA sequencing with solid-state nanopores has been investigated intensively in recent time. However, the area still confronts problems and challenges. In this work, we present a brief overview of computational studies of key issues in DNA sequencing with solid-state nanopores by addressing the progresses made in the last few years. We also highlight future challenges and prospects for DNA sequencing using this technology.